Diazoxide Post-conditioning Activates the HIF-1/HRE Pathway to Induce Myocardial Protection in Hypoxic/Reoxygenated Cardiomyocytes - Chen, Xi-Yuan; Wang, Jia-Qi; Cheng, Si-Jing; Wang, Yan; Deng, Meng-Yuan; Yu, Tian; Wang, Hai-Ying; Zhou, Wen-Jing (Frontiers in Cardiovascular Medicine, 2021)
Background: Previous studies have shown that diazoxide can protect against myocardial ischemia-reperfusion injury (MIRI). The intranuclear hypoxia-inducible factor-1 (HIF-1)/hypoxia-response element (HRE) pathway has been shown to withstand cellular damage caused by MIRI. It remains unclear whether diazoxide post-conditioning is correlated with the HIF-1/HRE pathway in protective effect on cardiomyocytes. Methods: An isolated cardiomyocyte model of hypoxia-reoxygenation injury was established. Prior to reoxygenation, cardiomyocytes underwent post-conditioning treatment by diazoxide, and 5-hydroxydecanoate (5-HD), N-(2-mercaptopropionyl)-glycine (MPG), or dimethyloxallyl glycine (DMOG) followed by diazoxide. At the end of reoxygenation, ultrastructural morphology; mitochondrial membrane potential; interleukin-6 (IL-6), tumor necrosis factor alpha (TNF-α), reactive oxygen species (ROS), and HIF-1α levels; and downstream gene mRNA and protein levels were analyzed to elucidate the protective mechanism of diazoxide post-conditioning. Results: Diazoxide post-conditioning enabled activation of the HIF-1/HRE pathway to induce myocardial protection. When the mitoKATP channel was inhibited and ROS cleared, the diazoxide effect was eliminated. DMOG was able to reverse the effect of ROS absence to restore the diazoxide effect. MitoKATP and ROS in the early reoxygenation phase were key to activation of the HIF-1/HRE pathway. Conclusion: Diazoxide post-conditioning promotes opening of the mitoKATP channel to generate a moderate ROS level that activates the HIF-1/HRE pathway and subsequently induces myocardial protection.